HIV status, knowledge of mother-to-child transmission of HIV and antenatal care use among Ethiopian women - Ida Sahlu; Chanelle J. Howe; Melissa A. Clark; Brandon D.L. Marshall (Springer, 2019)
Objective: To determine whether HIV status and knowledge of mother-to-child-transmission (MTCT) of HIV are associated with antenatal care (ANC) use. Methods: Data were obtained from the 2011 Ethiopia Demographic and Health Survey among women aged 15-49 years who agreed to HIV testing and who reported giving birth in the preceding five years. The two exposures of interest were HIV status and knowledge of MTCT. Unadjusted and adjusted prevalence ratios for ANC use were estimated by fitting modified Poisson regression models. Results: Among the 7392 women in the sample, ANC use was lowest among HIV-negative, low MTCT knowledge women (31.6% [95% confidence interval: 28.1-35.1]), and highest among HIV-positive, high knowledge women (81.9% [69.8-94.0%]). ANC use was significantly higher among HIV-positive, high knowledge (adjusted prevalence ratio [APR] = 1.60 [1.32-1.94]) and HIV-negative, high knowledge women (1.37 [1.24-1.51]) compared with HIV-negative, low knowledge women. There was no statistically significant difference in ANC use by HIV status among low knowledge women (1.26 [0.71-2.25]). Conclusions: HIV-positive women generally had better MTCT knowledge. Among HIV-negative women, the prevalence of ANC use was greater among women with higher knowledge. Increasing MTCT knowledge may facilitate ANC use and in turn may eliminate MTCT.